Physico-chemical properties of different kind of rice water and their effect on diarrhoea causing bacteria and dandruff causing fungi - Awasthi, Shruti; Das, Anwesha; Bhattacharjee, Chumki (Journal of Phytology, 2011)
Rice water has been used for curing various ailments. The experiment was conducted to know the physico-chemical and cooking properties of six fine rice varieties. Length and breadth of the reported varieties ranges from 6Ã¢â‚¬â€œ7.8mm and 4.5Ã¢â‚¬â€œ5.5mm. The highest amylose (28%) was estimated in Gobindo bhog non - boiled rice followed by Sona Masori half boiled rice (24.2%) and lowest (18.6%) were Saffola arise active rice and Kerala rice. Alkali spreading value ranges from 3.0 to 3.9 of the tested varieties. Cooking time varied from 11min to 31min among the tested rice varieties. Elongation ratio of the fine rice varieties ranges from 1.5 to 2.4. Rice water of Kerala rice, Saffola arise active rice and full boiled rice had shown the significant zone of against diarrhoea causing bacteria. Overnight and 1 hr shocked rice water had shown the effective result against the dandruff causing fungi.Ã‚Â